Pengaruh Kualitas Pelayanan terhadap Loyalitas dengan Kepuasan Pelanggan sebagai Pemediasi di Larissa Aesthetic Center Cabang Madiun - - Feberiana (Fakultas Bisnis, 2016)
Quality of service which is optimal to be expected can fulfill custumer expectation so that create satisfaction and influence custumer loyalty at company. This research aim to test indirect and direct influence is quality of service to loyalty with satisfaction of custumer as mediationi in Larissa Aesthtetic Center Madiun jl. Perintis kemerdekaan No 12. The sample used in this research amounted to 100 respondents . The sampling technique using accidental sampling. Test equipment used was SPSS 17. The results of the analysis indicate (1) the quality of services and significant positive effect on customer satisfaction; (2) quality of service and significant positive effect on customer loyalty; (3) custumer satisfaction and significant positive effect on customer loyalty; (4) the quality of services and significant positive effect on customer loyalty through customer satisfaction.